AN EXPERIMENTAL INVESTIGATION ON THE PERFORMANCE OF RUBBERIZED FLY ASH BRICKS MANUFACTURED USING WASTE RUBBER - Jyoti Sorout; Dilraj Preet Kaur; Seema Raj (Proceedings on Engineering Sciences, 2024)
Waste tyres have a substantial detrimental influence on the environment owing to their considerable volume, non-biodegradability, susceptibility to combustion, and function as a breeding habitat for mosquitoes and several other pests. The use of waste tyre rubber (WTR) for the production of environmentally-friendly rubberized fly ash bricks serves as a method for mitigating the issue of waste disposal, so contributing to the reduction of resource depletion and environmental deterioration. The aim of this study was to evaluate the practicality of using waste tyre rubber (WTR) as a partial replacement for sand in the manufacturing of rubberized fly ash bricks. The purpose was to provide evidence that WTR waste may be effectively used in the construction sector. Waste tyre rubber (WTR) was used as a substitute for sand, with proportions ranging from 10% to 30%. The effectiveness of the green rubberized fly ash bricks was evaluated by analyzing its compressive strength, water absorption, porosity, thermal conductivity, and microscopic properties. The results of this research suggest that the compressive strength of rubberized bricks decreased somewhat in proportion to the extent of replacement. At a sand replacement rate of 10% with waste tyre rubber (WTR), the bricks exhibited the greatest compressive strength of 10.73 MPa and water absorption rate of 16.68%. The findings indicate that WTR exhibits promise as a viable option for replacing up to 30% of sand in the production of environmentally sustainable construction bricks.